(untitled) (Perner’s Contacts, 2012)
The impacts of aviation on the environment are not negligible. Various systems in aviation are interrelated, so it is necessary to make decisions based on adequate and comprehensive information base. Tools of AETS (Aviation Environmental Tools Suite) method developed by FAA in cooperation with NASA allow components through EDS, AEDT, APMT-Economics, APMT-Impacts and APMTCost Benefit evaluate the financial costs, environmental impacts of decisions and consideration of their advantages. Appropriate implementation of environmental measures and investments may even provide aviation operators or airports cost savings and significant improvement of aviation impacts on the environment.